Membrane type 1-matrix metalloproteinase promotes human prostate cancer invasion and metastasis - Cao, Jian; Chiarelli, Christian; Kozarekar, Pallavi; Adler, Howard L. (Thrombosis and Haemostasis, 2005)
Development of metastases requires cancer cells to breach underlying basement membrane, migrate through interstitial stroma and gain access to blood or lymphatic vessels. Membrane type 1-matrix metalloproteinase (MT1-MMP) has been linked with these processes. Expression of MT1-MMP in human prostate cancer correlates with the stage of this disseminated disease. The mechanism underlying this observation, however, still remains to be understood. To study the role of MT1-MMP in prostate cancer dissemination, endogenous and recombinant MT1-MMP expressed in human prostate cancer cell lines (DU-145 and LNCaP) were examined. Using FITC-labeled Ma-trigel, a soluble basement membrane extract coated coverslips, LNCaP cells stably expressing a chimera of MT1-MMP and Green Fluorescent Protein (MT1-GFP) degraded Matrigel and readily migrated over degraded substrates. The degradation of Matrigel by LNCaP cells expressing MT1-GFP was sensitive to MMP inhibitors, CT-1746 and TIMP-2, but not TIMP-1. Cell migration was dramatically enhanced by expression of MT1-MMP. By employing surgical orthotopic implantation of LNCaP cells stably expressing MT1-GFP into the prostate gland of immunodeficient mice, we demonstrated that MT1-MMP promotes lymph node and lung metastasis of prostate cancer cells. Together, these results emphasize the pivotal role of MT1-MMP in prostate cancer dissemination and confirm that MT1-MMP is a suitable target to prevent cancer metastasis.
Keywords: MT1-MMP; cell migration; invasion; metastasis; prostate cancer